 My Math Forum If A, B independent events. Then A and B^C, as well as, A^C and B are independent
 User Name Remember Me? Password

 Probability and Statistics Basic Probability and Statistics Math Forum

 June 9th, 2015, 09:10 AM #1 Senior Member   Joined: Jan 2013 From: Italy Posts: 154 Thanks: 7 If A, B independent events. Then A and B^C, as well as, A^C and B are independent Hi, I want to prove the following, but I encounter some problems. Can you give me any suggestions? Let A, B be independent events. Show that $\displaystyle A$ and $\displaystyle B^C$ are independent. I have done some things but without success: So, we have to show that $\displaystyle P(A \cap B^C) = P(A) \cdot P(B^C)$. Let: $\displaystyle P(A) = x \Rightarrow P(A^C) = 1 - P(A) = 1- x, \\ P(B) = y \Rightarrow P(B^C) = 1 - P(B) = 1 - y$ Since A, B are independent events we have: $\displaystyle P(A \cap B) = P(A) \cdot P(B) = x \cdot y$ So here we want to know: "In what way do we can rewrite $\displaystyle P(A \cap B^C)$, from the math data available?" I have tried this, using DeMorgan, but without obtain what I needed: $\displaystyle P[(A^C \cup B)^C] = P[(A^C)^C \cap B^C] = P(A \cap B^C) = 1 - P(A^C \cup B) =$ here I'm not sure if the addition rule can be applied, however: $\displaystyle = 1 - [P(A^C) + P(B) - P(A^C \cap B)]$ but here I don't have any $\displaystyle P(A^C \cap B)$ term to substitute using x,y. So I don't know how to proceed! Can you give any suggestions? Many thanks! June 9th, 2015, 01:33 PM #2 Senior Member   Joined: Jan 2013 From: Italy Posts: 154 Thanks: 7 for clarity I post here another proof, because it is from the following one that I have to prove what I have written in the first post: Suppose $\displaystyle A$ and $\displaystyle B$ are independent events. Then $\displaystyle A^C$ and $\displaystyle B^C$ are independent events. We have to show that $\displaystyle P(A^C \cap B^C) = P(A^C) \cdot P(B^C)$. Let: $\displaystyle P(A) = x \Rightarrow P(A^C) = 1 - P(A) = 1- x, \\ P(B) = y \Rightarrow P(B^C) = 1 - P(B) = 1 - y$ Since A, B are independent events we have: $\displaystyle P(A \cap B) = P(A) \cdot P(B) = x \cdot y$ By the addition rule: $\displaystyle P(A \cup B) = P(A) + P(B) - P(A \cap B) = x + y - xy$ Using DeMorgan law: $\displaystyle P(A^C \cap B^C) = P[(A \cup B)^C] = 1 - P(A \cup B) = 1 - x - y + xy.$ And also: $\displaystyle P(A^C) \cdot P(B^C) = (1-x)(1-y) = 1-x-y+xy$ END. Similarly, I have tried to show in the first post that A and B^C, as well as A^C and B are independent, but without success. Can you give me any helping hand? many thanks! Last edited by beesee; June 9th, 2015 at 01:37 PM. June 9th, 2015, 01:52 PM #3 Global Moderator   Joined: May 2007 Posts: 6,705 Thanks: 670 P(A)=P(A∩B)+P(A∩B')=P(A)P(B)+P(A∩B') (B and B' are disjoint and add to entire space) P(A∩B')=P(A)(1-P(B))=P(A)P(B') Thanks from beesee Tags events, independent ### A~B then P(A)~P(B)

Click on a term to search for related topics.
 Thread Tools Show Printable Version Email this Page Display Modes Linear Mode Switch to Hybrid Mode Switch to Threaded Mode Similar Threads Thread Thread Starter Forum Replies Last Post Abstract3000 Algebra 1 February 16th, 2014 12:25 PM Keroro Algebra 1 June 6th, 2012 08:17 AM daivinhtran Algebra 1 April 10th, 2011 01:07 PM finitehelp Algebra 1 September 22nd, 2009 06:49 PM Siria Advanced Statistics 4 July 5th, 2009 09:21 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top      